Education On "Zero Waste" Waste Management Based On The 3 R Approach In Jakarta Coastal Area: Edukasi Pengelolaan Sampah "Zero Waste" Berdasarkan Pendekatan 3 R Di Daerah Pesisir Jakarta - Wijaya, Meiliyana; Dewi, Rita Dewi; Joprang, Freggy Spicano Joprang; Siladjaja, Gabrielle Kyra Allegra; Hananta, Linawati Hananta (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Efforts to manage waste properly require active participation from the community in maintaining the preservation and sustainability of the earth. Over the past decade, various countries, including Indonesia, have adapted their waste management system to the zero-waste principle. This system applies the 3R principle (Reduce, Reuse, Recycle) in handling waste. Household waste generated by the people of the coastal area of Jakarta, especially the Kalibaru Village, Cilincing, has created a pile of garbage that has polluted the area. Community service programs in the form of education on waste management activities with this principle need to be carried out to increase public awareness of sustainably protecting the environment. The implementation of counseling activities is carried out by presenting "Zero waste" material with a "3R" approach with the lecture method, followed by a question-and-answer session, a quiz competition, and a competition to make multi-purpose stationery containers from cardboard and paper. Educational activities and craft-making contests are expected to increase the knowledge, understanding, and creativity of the Family Welfare Empowerment (PKK) regarding waste management and to become ambassadors for change for others in their area.